Управління ризиками як напрям забезпечення конкурентоспроможності підприємства - Тебенко, Віта Миколаївна; Болтянська, Лариса Олексіївна; Лисак, Оксана Іванівна; Tebenko, Vita; Boltianska, Larysa; Lysak, Oksana (Запоріжжя : 2023, 2023)
UA: У статті розглядається вплив ризикових чинників на конкурентоздатність підприємств. Подано визначення ризику та основні його види, які можуть впливати на діяльність підприємства. Аналізуються особливості сучасних ризиків. Розглядається питання соціальної відповідальності підприємств. Надається інформація про механізми управління ризиками, а також визначаються основні способи та прийоми впливу на ризик. EN: Тask statement. The aim of the article is to investigate risk management peculiarities and determine their impact on the competitiveness of an enterprise. Research results. The article analyzes the characteristics of modern risks, including technological changes, globalization, dynamic markets, environmental threats, pandemics, political unrest, social risks, and financial instability. Internal factors contributing to the emergence of risks in the enterprise, which play a key role in shaping its competitiveness and resilience, are identified. The risk management mechanism encompasses a set of measures for risk identification, assessment, and minimization. The most common means and techniques to influence risks include risk reduction, preservation, transfer, avoidance, acceptance, prevention, and mitigation. The article identifies and analyzes the main directions for effectively reducing risks during project implementation, including risk assessment, the development of contingency plans, efficient time management, the utilization of modern technologies and tools, and the development of team competencies. Conclusion. Effective risk management requires all project participants to realize that the real risk lies not in the execution of modern projects but in their abandonment, which may lead to a loss of competitiveness and market positions in the future. The competitiveness of modern enterprises depends on their ability to manage potential risks effectively. Enterprises that take risks into account can adapt to changes more rapidly, develop strategies to counter adverse impacts, and implement flexible business models. Risk consideration opens up new opportunities for innovation and the creation of competitive advantages, forming the basis for successful competitiveness in the dynamic contemporary business environment.
Risk management as a direction of ensuring the competitiveness of the enterprise
Keywords: ризик; небезпека; загрози; конкурентоспроможність; управління; ймовірність; контроль; оцінка; невизначеність; risk; hazard; threats; competitiveness; management; probability; control; assessment; uncertainty